Descripción y daños de las plagas que atacan el fríjol [conjunto audiotutorial] - Ospina O., Héctor Fabio; Schoonhoven, Aart van; Gómez, Luis Alberto; Valderrama, Rafael (International Center for Tropical Agriculture, 1979)
This audiotutorial unit (cassette, printed script, 80 color slides, study guide, self-evaluation test), prepared by the Communications Support Unit at CIAT, is available for use with a manually or automatically synchronized slide projector/cassette tape recorder. Each unitis available from the Distribution Office at a cost of US$50; photocopies of the study guide alone can be obtained from the Bean Information Center. Pests are one of the main factors limiting bean production. Of the 200 species of insects and mites, however, only a few cause losses of economic importance. Severity of attack depends on environmental conditions, var., planting date and other agronomic practices. The principal pests described and illustrated are (a) those attacking seedlings: Hylemya cilicrura, Elasmopalpus lignosellus, cutwoms (Agrotis sp., Prodenia sp., Acrolopus sp.), Gryllus assimilis, Phyllophaga and slugs (Vaginilus plebejus, Limax maximus); (b) leaf eaters: (Epilachna varivestis, Diabrotica sp., Cerotoma sp., Systena sp., Epitrix sp. Neobrolica sp., Urbanus proteus, Hedylepta indicata, Trichoplusia ni, Estigmene acrea); leaf piercers (Empoasca kraemeri, Gargaphia sanchezi, Bemisia spp., Aphis sp., Macrosiphum sp., Tetranychus desertorum, Polyphagotarsonemus latus); (c) leaf miners (Agromyza sp., Hemichalepus sp.; (d) pod- attacking insects: Apion godmani, Epinotia opposita, Maruca testulalis, Laspeyresia leguminis, Heliothis spp.; (e) stored grain pests: Acanthoscelides obtectus, Zabrotes subfasciatus. (CIAT)